KARAKTERISTIK DAN KERAGAMAN MIKROBA UNIT PENGOLAH LIMBAH CAIR TEKSTIL - Wage Komarawidjaja (Jurnal Teknologi Lingkungan, 2007)
One of major pollutants in textile wastewaters is organic substance that could be degraded and utilized by microbe as nutrient and energy source in activated sludge compartment at textile waste water treatment unit. Therefore, microbe is the concern in this observation. Based on the characterization result, such as colony type, Gram stain and microbial shape, there are 13 type of microbegrow in activated sludge. From 13 microbial type, 5 isolates is possibly as Bacillus spp., 4 isolates is to be Flavobacterium spp. and the rest as Pseudomonadaceae.